An air chargeable hydrogen battery by reversible electrochemical trapping of the protons. Issue 22 (31st October 2022) - Christudas Dargily, Neethu; Thimmappa, Ravikumar; Devendrachari, Mruthunjayachari Chattanahalli; Thotiyl, Musthafa Ottakam
Abstract : An air chargeable hydrogen battery is demonstrated by reversible trapping of the protons, in a hydrogen carrying quinone moiety. Charging the battery with ambient air without any electrical supply, adds an extra handle to battery functionality. Abstract : We show an air-chargeable hydrogen battery chemistry wherein the two major aspects of hydrogen economy such as hydrogen storage and its utilization are combined in a single device. During the discharge chemistry, the battery electrochemically traps the protons in a hydrogen-carrying quinone moiety while delivering electric power. The redox energy positioning of molecular oxygen above that of the reversible proton-coupled electron transfer in the quinone moiety uniquely allows the charging of the battery with ambient air during concomitant electrical power production. The prospects of charging the battery with ambient air without the necessity of an external voltage will be immensely useful for isolated/rural areas and military operations in challenging geography.